A single-point mutation in the rubella virus E1 glycoprotein promotes rescue of recombinant vesicular stomatitis virus - Pratyush Kumar Das; Paulina Alatriste Gonzalez; Rohit K. Jangra; Peiqi Yin; Margaret Kielian (mBio, 2024)
ABSTRACT Rubella virus (RuV) is an enveloped plus-sense RNA virus and a member of the Rubivirus genus. RuV infection in pregnant women can lead to miscarriage or an array of severe birth defects known as congenital rubella syndrome. Novel rubiviruses were recently discovered in various mammals, highlighting the spillover potential of other rubiviruses to humans. Many features of the rubivirus infection cycle remain unexplored. To promote the study of rubivirus biology, here, we generated replication-competent recombinant VSV-RuV (rVSV-RuV) encoding the RuV transmembrane glycoproteins E2 and E1. Sequencing of rVSV-RuV showed that the RuV glycoproteins acquired a single-point mutation W448R in the E1 transmembrane domain. The E1 W448R mutation did not detectably alter the intracellular expression, processing, glycosylation, colocalization, or dimerization of the E2 and E1 glycoproteins. Nonetheless, the mutation enhanced the incorporation of RuV E2/E1 into VSV particles, which bud from the plasma membrane rather than the RuV budding site in the Golgi. Neutralization by E1 antibodies, calcium dependence, and cell tropism were comparable between WT-RuV and either rVSV-RuV or RuV containing the E1 W448R mutation. However, the E1 W448R mutation strongly shifted the threshold for the acid pH-triggered virus fusion reaction, from pH 6.2 for the WT RuV to pH 5.5 for the mutant. These results suggest that the increased resistance of the mutant RuV E1 to acidic pH promotes the ability of viral envelope proteins to generate infectious rVSV and provide insights into the regulation of RuV fusion during virus entry and exit.IMPORTANCERubella virus (RuV) infection in pregnant women can cause miscarriage or severe fetal birth defects. While a highly effective vaccine has been developed, RuV cases are still a significant problem in areas with inadequate vaccine coverage. In addition, related viruses have recently been discovered in mammals, such as bats and mice, leading to concerns about potential virus spillover to humans. To facilitate studies of RuV biology, here, we generated and characterized a replication-competent vesicular stomatitis virus encoding the RuV glycoproteins (rVSV-RuV). Sequence analysis of rVSV-RuV identified a single-point mutation in the transmembrane region of the E1 glycoprotein. While the overall properties of rVSV-RuV are similar to those of WT-RuV, the mutation caused a marked shift in the pH dependence of virus membrane fusion. Together, our studies of rVSV-RuV and the identified W448R mutation expand our understanding of rubivirus biology and provide new tools for its study.